2009
DOI: 10.1537/ase.070915
|View full text |Cite
|
Sign up to set email alerts
|

Foot deformations under different load-bearing conditions and their relationships to stature and body weight

Abstract: Footwear comfort is primarily determined by the fit between the foot and the shoe. Foot deformations that cannot be accommodated by the flexibility of the material of the shoe upper have to be dealt with by other adaptive means. The major purpose of this study was to determine foot deformations using nine foot dimensions-foot length, arch length, foot width, midfoot width, heel width, midfoot height, medial malleolus height of the most protruding point, lateral malleolus height of the most protruding point and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
65
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 25 publications
9
65
0
Order By: Relevance
“…This may require the wearers to select a larger shoe size (and therefore length) to accommodate their extra foot width and, since the inclusion criteria was use of a size EU 43 shoe, this would explain the comparatively shorter feet in the obese group. This is consistent with work which identified a strong correlation between body mass and foot width (r = 0.782, p < .05; Xiong et al, 2009). Additionally it has been demonstrated that when weight bearing the foot width increases more than foot length (Xiong et al, 2009).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This may require the wearers to select a larger shoe size (and therefore length) to accommodate their extra foot width and, since the inclusion criteria was use of a size EU 43 shoe, this would explain the comparatively shorter feet in the obese group. This is consistent with work which identified a strong correlation between body mass and foot width (r = 0.782, p < .05; Xiong et al, 2009). Additionally it has been demonstrated that when weight bearing the foot width increases more than foot length (Xiong et al, 2009).…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with work which identified a strong correlation between body mass and foot width (r = 0.782, p < .05; Xiong et al, 2009). Additionally it has been demonstrated that when weight bearing the foot width increases more than foot length (Xiong et al, 2009). …”
Section: Discussionsupporting
confidence: 90%
“…Foot shape variations exist between genders. Men have longer and wider feet compared to women when the foot length and width are normalized with respect to stature (Wunderlich and Cavanagh, 2000;Ashizawa et al, 1997;Xiong and Goonetilleke, 2007).…”
Section: Participantsmentioning
confidence: 99%
“…The par# cipant was under the weight-bearing condi# on of half body-weight (HWB) [15], and the external shape of each foot was laser scanned respec# vely and captured by eight cameras. In the HWB condi# on, the par# cipant was in a balance standing posture with barefoot and eyes focused straight ahead for equal loads on both foot.…”
Section: Methodsmentioning
confidence: 99%